Effect of Traumatic Reticuloperitonitis on Some Protein and Enzyme of Liver in Local Cow - Khalid Ah. Ha. Al-saedy; Montasser Mo. He. Al-obaydy (Tikrit Journal of Pure Science)
The current study was designed to determine the changes in a number of biochemical parameters associated with infection of traumatic reticuloperitonitis in the local cows The blood sample is pulled 80 of those cows which included two groups, the first group included 16 animals represented the control group, and the second group included 64 animals suffering from inflammation of traumatic reticuloperitonitis. The results showed that the infection of traumatic reticuloperitonitis increased significantly (P <0.05) in the concentration of Haptpglobin and activity of the Creatine Kinase enzyme and enzyme of ceruloplasmin and incidence  significant decrease in the activity of the enzyme Alanine Aminotransferase and the enzyme of Aspartate Aminotransferase compared with the control group. This study concludes that inflammation of traumatic  reticuloperitonitis effect directly on the liver, where it led to the rise of some indicators of inflammation and reduced some enzymes from normal value.